2012
DOI: 10.1128/aac.00500-12
|View full text |Cite
|
Sign up to set email alerts
|

Rifapentine Is Not More Active than Rifampin against Chronic Tuberculosis in Guinea Pigs

Abstract: e Rifamycins are key sterilizing drugs in the current treatment of active tuberculosis (TB). Daily dosing of rifapentine (P), a potent rifamycin with high intracellular accumulation, in place of rifampin (R) in the standard antitubercular regimen significantly shortens the duration of treatment needed to prevent relapse in a murine model of active TB. We undertook the current study to compare directly the activities of human-equivalent doses of P and R in a guinea pig model of chronic TB, in which bacilli are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 38 publications
3
33
1
Order By: Relevance
“…In addition, the outcome for INH was similar to that in the report from Hoff et al (a 1.71-log reduction compared with an ϳ1.6-to 1.7-log reduction) (39). Similar differences in the outcomes in guinea pigs were also found for RIF when our data at a dose of 25 mg/kg were compared with those in a report of RIF at a dose of 50 mg/kg (40). The reason for different results among groups is unknown, but the methodological differences, such as bacterial strains, breeding conditions, and the time of initiation of the treatment, could be considerable.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, the outcome for INH was similar to that in the report from Hoff et al (a 1.71-log reduction compared with an ϳ1.6-to 1.7-log reduction) (39). Similar differences in the outcomes in guinea pigs were also found for RIF when our data at a dose of 25 mg/kg were compared with those in a report of RIF at a dose of 50 mg/kg (40). The reason for different results among groups is unknown, but the methodological differences, such as bacterial strains, breeding conditions, and the time of initiation of the treatment, could be considerable.…”
Section: Discussionsupporting
confidence: 77%
“…Steady-state PK values of RIF and RFP (Table 1) differed from those of single-dose studies (1,7). The C max and AUC were significantly increased at the steady state for both RFP and RIF compared to single-dose data.…”
mentioning
confidence: 60%
“…The C max and AUC were significantly increased at the steady state for both RFP and RIF compared to single-dose data. In the present study, we determined metabolite concentrations from serum samples obtained in earlier single-dose studies (1) and found that desRFP was absent in guinea pigs that received a single dose of RFP of 10 or 50 mg/kg but present in 2 of 3 animals that received a single dose of 100 mg/kg. The guinea pig in which desRFP serum concentrations were undetectable following a single dose of RFP at 100 mg/kg was found to have significantly lower serum RFP concentrations than those of the other two animals receiving the same dose (data not shown).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trial simulations demonstrate that splitting the dose or taking the dose with food could substantially increase daily RFP exposures, which is a significant finding, given that RFP's activity appears to correlate best with AUC/MIC and that current dosing achieves concentrations that are still on the steep part of the dose-response curve. The dose-response relationship was reported in mouse studies (20), guinea pig studies (21), and patient early bactericidal activity studies (22). Most importantly, preliminary results from the recently completed phase IIb TBTC trial 29X in patients suggests a pronounced exposure-response relationship, where the time to culture conversion on solid and liquid media was best predicted by rifapentine exposure (23).…”
Section: Figmentioning
confidence: 95%